FEATURES OF MUTUAL FUNCTION OF WORD GROUPS IN ENGLISH AND UZBEK LANGUAGES (The Role of Exact Sciences in the Era of Modern Development, 2024)
In the article, the features of mutual function of word groups in the English and Uzbek languages, their theoretical aspects are shown, as well as the importance of word formation in both languages, their similarities and differences are mentioned.